Elaboration of a bioplastic with corn starch/glycerol/maleic anhydride/polycaprolactone: preliminary study: estudio preliminar - Maldonado-Santoyo, Maria (2025)
This work presents the results obtained in the preparation of a bioplastic using corn starch, glycerol, maleic anhydride and polycaprolactone (Alm/G/Am/PCL). For  this, three mixtures were prepared: M1(Alm/G), M2(Alm/G/Am) and M3(Alm/G/Am/PCL) using a kitchen mixer. They were then processed in a twin-screw extruder (80 rpm) and a temperature profile between 75-112°C. The filaments obtained were cooled and cut and, by molding with a hydraulic press (130°C/20,000lbf/3min) the sheets, were obtained. The bioplastics were characterized in some mechanical properties, infrared analysis, water absorption, color and aerobic primary biodegradability in aqueous medium. The results show stress values ​​at break 1.40±0.10, 1.12±0.07 and 0.38±0.06 MPa; strain of break 23.36±2.3, 20.46±2.6 and 22.33±1.6% and, modulus of elasticity of 1.31±0.39, 1.43±0.16 and 2.74±0.18 MPa for M1, M2 and M3, respectively. The most prominent molecular interaction was the change in carbonyl group. The water absorption for all mixtures exceeded 60% (26h) and the primary biodegradability achieved was between 30-34%. Bioplastics M2 and M3 improved some mechanical properties with the addition of maleic anhydride and polycaprolactone. All bioplastics presented good processability by extrusion at the proposed conditions.